Health Belief Model tentang Upaya Pencegahan Perilaku Seks Bebas pada Remaja - Kustin, Kustin; Handayani, Yuni (Puslitbang Sinergis Asa Professional, 2024)
Sexual behavior among adolescents can have social and psychological impacts on them. As an effort to prevent free sex, both internal and external measures can be taken, one of which is self-control using the Health Belief Model (HBM) approach to predict the causes of their behavior. The purpose of this study is to determine the influence of factors such as perceived susceptibility, perceived severity, cues to action, perceived benefits, and perceived barriers on the efforts to prevent free sex conducted at SMK dr. Soebandi. This research method uses a quantitative cross-sectional design with a sample size of 100 respondents selected through simple random sampling. Data were collected using a questionnaire. Data analysis was performed using logistic regression. The results of statistical tests showed significance in the variables of perceived susceptibility (p=0.000), perceived severity (p=0.000), cues to action (p=0.000), and perceived benefits (p=0.000), but not significant for perceived barriers (p=0.144). The conclusion of the study is that perceived susceptibility, perceived severity, cues to action, and perceived benefits have an influence on the efforts to prevent free sex among adolescents, whereas perceived barriers have no relationship with the efforts to prevent free sex among adolescents.